Comparative study of wood flour photodegradation of two wood species submitted to artificial weathering - Poletto, Matheus (Maderas. Ciencia y Tecnología, 2017)
In this work Eucalyptus grandis and Dipteryx odorata were submitted to photodegradation by ultraviolet radiation. The effect of ultraviolet radiation irradiation on the color change and chemical composition of each wood flour were evaluated. The samples were submitted to a total of 500h of artificial weathering using condensation stages and ultraviolet radiation B irradiation cycles. The changes in wood flour color were monitored by spectrocolorimetry, while the changes in wood chemical composition were evaluated by Fourier transform infrared spectroscopy. Both species showed changes in color with increased exposure time to artificial weathering. For both wood species the variation in color change was considered very appreciable after 500h. The Eucalyptus grandis specie showed appreciable color change after 120h, while for Dipteryx odorata specie the color change is appreciable only after 240h. The Fourier transform infrared spectroscopy results showed that lignin was strongly degrades by ultraviolet radiation radiation in both species. However, Dipteryx odorata was more resistant to photodegradation than Eucalyptus grandis, probably due to lower lignin content in this wood. The results clearly indicated that for the wood species studied the rate of weathering is influenced by wood species.